EFEKTIVITAS INTERVENSI MODIFIKASI PERILAKU DENGAN REINFORCEMENT POSITIF DAN NEGATIF PADA SISWA SLOW LEARNER: STUDI KASUS TUNGGAL - Riza Fitriana (Pelantar Press, 2025)
This research aims to optimize the capabilities of a slow learner student through behavior modification intervention using positive and negative reinforcement. The research subject is R, a 16-year-old eighth-grade MTs student with an IQ score of 81 (Wechsler scale), which falls in the below-average category and exhibits slow learner characteristics. The research method employs a Single Subject Research (SSR) design with repeated measurements of behavioral changes conducted over a two-week period. The results show significant changes in the subject's behavior after intervention, including: reduction in negligent behavior during pre-school activities, decreased tendency to ignore parental instructions to study, elimination of tardiness at school, and cessation of lying down during learning processes. The cooperative attitude of the subject, parents, and teachers became an important factor in the success of this intervention. This research contributes to understanding the effectiveness of behavior modification in addressing disciplinary problems in slow learner students through a structured and consistent individual approach